PERAN GANDA GURU PENDAMPING KHUSUS DAMPINGI ANAK LAMBAT BELAJAR DI SD WIROPATEN SURAKARTA - Giezka Khaleda Anindita (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2025)
This article examines the dual role of the Special Assistance Teacher (GPK) as a homeroom teacher in supporting the understanding of slow learners in inclusive education. This research is motivated by the limited number of GPKs, which requires them to carry out dual tasks. This affects the learning process of students with special needs. This study used a descriptive qualitative method and the data collection process was carried out at SD Negeri Wiropaten Surakarta through triangulation techniques. The results showed that the dual role of GPK as a homeroom teacher is very important in supporting the development of students with special needs in various aspects.